Porous graphene-based acid-resistant composite membrane and preparation method thereof

Through the interfacial polymerization method of functionalized graphene quantum dots and diisocyanate, a porous graphene-based acid-resistant composite film was prepared, which solved the problem of hydrolysis of polyamide film under extremely acidic conditions and achieved efficient membrane separation performance in an acidic environment.

CN119793238AActive Publication Date: 2025-04-11TIANJIN POLYTECHNIC UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510057548.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

Existing polyamide films are prone to hydrolysis under extremely acidic conditions, resulting in a degradation of membrane performance.

Method used

Functional graphene quantum dots were used as aqueous monomers and reacted with diisocyanate through interfacial polymerization to prepare a porous graphene-based acid-resistant composite film. The method includes dispersing the functionalized graphene quantum dots in an aqueous solution to contact the base film, then performing interfacial polymerization in the organic phase solution, and performing heat treatment to form a porous structure.

Benefits of technology

The prepared porous graphene-based acid-resistant composite membrane exhibits high permeability flux and high retention rate at low pressure, and remains stable in an acidic environment, and is suitable for the separation and purification of high acid materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793238A_ABST
    Figure CN119793238A_ABST
Patent Text Reader

Abstract

The invention discloses a porous graphene-based acid-resistant composite membrane and a preparation method thereof.The preparation method of the porous graphene-based acid-resistant composite membrane comprises the following steps that 1, functionalized graphene quantum dots are dispersed in an aqueous solution containing a surfactant to prepare an aqueous phase solution, the concentration of the functionalized graphene quantum dots in the aqueous phase solution is 0.1-20 g.L <-1 >; step 2, immersing a base membrane into the water phase solution, taking out the base membrane after soaking for a fixed time, and removing redundant liquid, preferably, removing the redundant liquid by using a rubber roller; step 3, immersing the base membrane treated in the step 2 into an organic phase solution of diisocyanate with the concentration of 0.1-20 g.L <-1 >, and carrying out interfacial polymerization reaction; and 4, carrying out heat treatment on the membrane obtained after treatment in the step 3 to obtain the porous graphene-based acid-resistant composite membrane. The high-temperature-resistant and corrosion-resistant resin has the characteristics of acid resistance, oxidation resistance, solvent resistance, pollution resistance and the like, is suitable for various separation scenes, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acid-resistant composite nanofiltration membranes, and in particular to a porous graphene-based acid-resistant composite membrane and a preparation method thereof. Background Art

[0002] With the expansion of the chemical industry, acidic wastewater is posing a serious threat to the environment and human health. Nanofiltration is a membrane separation technology with excellent separation performance, which is widely used in water softening, drinking water purification, wastewater recycling, etc. Some of these application scenarios involve acidic environments. These strong acids usually degrade membrane components by changing the morphology and physicochemical properties of membrane components, resulting in decreased membrane performance.

[0003] Interfacial polymerization is one of the methods for preparing high-selectivity and high-flux nanofiltration membranes. Commonly used aqueous monomers include piperazine and its derivatives, polyethyleneimine, m-phenylenediamine and polyols, and oil-phase monomers mostly use trimesoyl chloride, terephthaloyl chloride and isophthaloyl chloride. Although polyamide films prepared from traditional monomers are currently commonly used nanofiltration membranes, these membranes are unstable under extreme conditions, such as extremely low pH values ​​and high temperatures. The amide bonds present in the membrane are inherently susceptible to hydrolysis under harsh conditions, resulting in a serious reduction in membrane performance. Introducing functionalized graphene and its derivatives in the aqueous phase is expected to solve this problem.

[0004] Graphene is a two-dimensional crystal composed of sp2 hybridized carbon atoms. Through covalent modification, non-covalent modification and element doping, atoms or functional groups such as nitrogen, boron, phosphorus, oxygen, sulfur and halogen are introduced into graphene to change its elemental composition and form functionalized materials, such as graphene oxide (GO) and amino graphene (AG). By using quantum confinement effect and quantum size effect to regulate graphene from the perspective of microscopic morphology, zero-dimensional graphene quantum dots can be further obtained. Compared with two-dimensional graphene, it has outstanding advantages such as smaller size, larger specific surface area, and stronger hydrophilicity, and has better dispersion performance in aqueous or organic solvents. In addition, for graphene oxide quantum dots (GOQDs), it also has the advantages of wide source of raw materials, easy preparation, good biocompatibility, low toxicity, and environmental protection. Introducing GOQDs into the separation layer through interfacial polymerization can not only improve the hydrophilicity of the membrane, but also reduce the filtration resistance of the membrane. At the same time, the GOQDs nanoaggregates in the separation layer can effectively shorten the membrane path of water molecules by constructing unique water channels, further improving the membrane flux. Summary of the invention

[0005] The purpose of the present invention is to provide a porous graphene-based acid-resistant composite membrane and a preparation method thereof in view of the technical defect that the polyamide membrane in the prior art is easily hydrolyzed under acidic conditions.

[0006] The technical solution adopted to achieve the purpose of the present invention is:

[0007] A method for preparing a porous graphene-based acid-resistant composite film comprises the following steps:

[0008] Step 1: dispersing functionalized graphene quantum dots in an aqueous solution to prepare an aqueous solution, wherein the concentration of the functionalized graphene quantum dots in the aqueous solution is 0.1 to 20 g·L -1 ;

[0009] Step 2, immersing the basement membrane in the aqueous solution, taking out the basement membrane after immersion for a fixed time, and removing excess liquid, preferably, using a rubber roller to remove excess liquid;

[0010] Step 3: Immerse the basement membrane treated in step 2 in a solution having a concentration of 0.1 to 20 g·L -1 In an organic phase solution of diisocyanate, an interfacial polymerization reaction is carried out;

[0011] Step 4, heat-treating the membrane obtained after the treatment in step 3 to obtain a porous graphene-based acid-resistant composite membrane.

[0012] In the above technical solution, in step 1, the functionalized graphene quantum dots are graphene quantum dots containing reactive functional groups, have a particle size of 0.5 to 10 nm, and have typical zero-dimensional and two-dimensional characteristics. Preferably, the reactive functional groups are amino, hydroxyl, sulfonic acid, epoxy, carbonyl or carboxylic acid groups.

[0013] In the above technical solution, the aqueous phase solution in step 1 further contains a surfactant, and the surfactant is at least one of sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate, sodium secondary alkyl sulfonate, sodium dodecyl sulfonate or sodium fatty acid methyl ester sulfonate, and the concentration of the surfactant in the aqueous phase solution is 0.001 to 0.2 g·L -1 .

[0014] In the above technical solution, in step 2, the base membrane is at least one of polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, nylon or polytetrafluoroethylene ultra / microfiltration membrane.

[0015] In the above technical solution, in step 2, the soaking time is 5-15 minutes.

[0016] In the above technical solution, in step 3, the diisocyanate is at least one of p-phenylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,4-phenylene diisocyanate or lysine diisocyanate.

[0017] In the above technical solution, in step 3, the solvent of the organic phase solution is at least one of n-hexane, cyclohexane, n-heptane or isoalkane.

[0018] In the above technical solution, in step 3, the time of the interfacial polymerization reaction is 10 to 300 seconds.

[0019] In the above technical solution, in step 4, the heat treatment temperature is 40-50° C., and the treatment time is 5-15 minutes.

[0020] Another aspect of the present invention also includes a porous graphene-based acid-resistant composite membrane obtained based on the preparation method.

[0021] In the above technical solution, the porous graphene-based acid-resistant composite membrane includes a base membrane and a porous graphene membrane composited on the base membrane. The porous graphene membrane is assembled on the surface of the base membrane by functionalized graphene quantum dots through interfacial polymerization. The functional groups on the edges of the functionalized graphene quantum dots are connected to isocyanate through polyurethane and polyurea structures. The thickness of the porous graphene membrane is less than 50 nm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention uses zero-dimensional nanomaterial functionalized graphene quantum dots as the only aqueous phase monomer and diisocyanate as the oil phase monomer to prepare an ultra-thin porous graphene-based composite membrane by a traditional interfacial polymerization method. By adjusting the microscopic size and functional group characteristics of the nanomaterial, an ultra-thin, highly permeable, acid-resistant nanocomposite membrane can be prepared. The functionalized graphene quantum dots contain abundant reactive active centers, have the advantages of large specific surface area, good water solubility and biocompatibility, abundant reaction sites and easy modification. This gives the nanofiltration composite membrane high permeation flux and high retention rate at low pressure.

[0024] 2. Since the quantum dots have a smooth surface similar to graphene inside, and hydrophilic reactive groups are introduced through functionalization, a porous graphene membrane (separation layer) with a nearly vertical pore structure is assembled through interfacial polymerization. Combined with the low-friction smooth surface inside the graphene quantum dots, the permeation flux of the composite membrane can be greatly improved. This uniform high-density porous structure is different from the layered pore structure of the graphene layered membrane. While increasing the density of nanochannels in the vertical direction, it sharply reduces the length of the horizontal channel, greatly shortening the flow path length of the material penetrating the membrane, thereby significantly reducing the filtration resistance of the membrane and improving the separation efficiency.

[0025] 3. The present invention adds a surfactant to the aqueous phase system during the interfacial polymerization process to reduce surface tension, thereby further improving the retention rate. Specifically, it mediates the arrangement and aggregation of aqueous phase monomers at the interface, reduces the direct contact between isocyanate having a large number of unsaturated bonds and the aqueous phase system, reduces the probability of side reactions during the interfacial polymerization process, and is conducive to the formation of a complete and defect-free ultra-thin film, thereby ensuring a higher permeation flux while improving the retention rate. In addition, the addition of the surfactant can further reduce the thickness of the separation layer.

[0026] 4. In the porous graphene-based composite membrane prepared by the method of the present invention, the functional groups at the edges of the quantum dots in the separation layer are connected to the isocyanate by polyurethane and polyurea structures. This functional group structure has natural acid resistance, so that the prepared porous graphene-based composite membrane shows excellent acid resistance and stability without affecting the retention rate and flux, and is suitable for the separation and purification of high-acid material systems.

[0027] 5. The porous graphene-based acid-resistant composite membrane prepared by the method of the present invention has a more compact combination of the porous graphene layer and the base membrane with excellent properties such as acid resistance, oxidation resistance, and solvent resistance, because the remaining unreacted functional groups in the graphene quantum dots can form hydrogen bonds with the oxygen-containing groups on the base membrane, which is beneficial to the application of membrane separation in complex environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a transmission electron microscope image of graphene oxide quantum dots prepared in step 1 in Example 1, with an average size of 3.2 nm;

[0029] Figure 2 This is a transmission electron microscope image of the amino graphene quantum dots prepared in step 2 in Example 1, with an average size of 3.4 nm;

[0030] Figure 3 This is a surface electron micrograph of the porous graphene-based acid-resistant composite membrane prepared in Example 4;

[0031] Figure 4 This is a cross-sectional electron micrograph of the porous graphene-based acid-resistant composite membrane prepared in Example 4. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Example 1

[0034] In this embodiment, the functionalized graphene quantum dots include graphene oxide quantum dots and amino-modified graphene quantum dots, and the mass ratio of the two is 1:2.

[0035] A method for preparing a porous graphene-based acid-resistant composite film comprises the following steps:

[0036] Step 1, synthesis of graphene oxide quantum dots: 0.2g of graphene oxide is dispersed in 100mL of distilled water, and then 100mL of hydrogen peroxide is added to the graphene oxide aqueous dispersion. After sufficient mixing, the mixture is reacted under an ultrasonic environment for 3h to ensure that the hydrogen peroxide can fully cut the graphene oxide. Subsequently, the mixture dispersion is filtered with a sand core filter equipped with a 0.22μm polytetrafluoroethylene microfiltration membrane to remove larger graphene oxide sheets. After filtration, a light brown graphene oxide quantum dot solution is obtained. Its transmission electron microscope image is as follows Figure 1 As shown, the particle size distribution of graphene oxide quantum dots is in the range of 2-5 nm, the particle size distribution range is narrow, and the average particle size is about 3.2 nm.

[0037] Step 2, synthesis of amination graphene quantum dots: Disperse 45 mg of graphene oxide in 45 mL of distilled water, then add 15 mL of ammonia water to the graphene oxide aqueous dispersion, and fully disperse and mix under an ultrasonic environment. After mixing evenly, transfer the dispersion to a reactor, seal it and place it in a muffle furnace at 120°C for chemical cutting reaction, and the reaction lasts for 5 hours. After the reaction is completed, cool to room temperature, filter using a polyethersulfone filter membrane with a pore size of 0.22 μm, and obtain amination graphene quantum dot powder after freeze-drying. Its transmission electron microscope image is as follows Figure 2 As shown, the particle size distribution of amino graphene quantum dots is in the range of 2-4 nm, the particle size distribution range is narrow, and the average particle size is about 3.4 nm.

[0038] Step 3, preparation of porous graphene-based acid-resistant composite membrane: The graphene oxide quantum dots and amino-modified graphene quantum dots prepared by hydrothermal method were prepared into a solution with a concentration of 1.0 g·L -1 Then, the two solutions were mixed in a ratio of 1:2 and a concentration of 0.01 g·L -1 The amphiphilic surfactant sodium dodecyl sulfate was added to obtain a mixed aqueous phase solution. The polyethersulfone-based membrane was then immersed in the mixed aqueous phase solution for 5 min. After removing the excess liquid with a rubber roller, the membrane was immersed in a solution with a concentration of 1.0 g·L -1 The interfacial polymerization reaction was carried out in an organic solution of p-phenylene diisocyanate for 3 minutes. After the reaction was completed, the obtained membrane was placed in an oven at 45°C for heat treatment for 10 minutes to finally obtain a porous graphene-based acid-resistant composite membrane.

[0039] This embodiment adopts a top-down method, chemically cutting graphene oxide with ammonia water to obtain amino graphene quantum dots, and cutting graphene oxide with hydrogen peroxide to obtain graphene oxide quantum dots, and using these as aqueous phase monomers and diisocyanate as organic phase monomers to regulate the interfacial polymerization reaction conditions, and adopting traditional interfacial polymerization methods to prepare a porous graphene-based acid-resistant composite film containing polyurethane and polyurea structures.

[0040] The porous graphene-based acid-resistant composite membrane prepared in this example was subjected to 1.0 g·L -1 The interception rate of Congo red solution was 97.38% and the permeation flux was 223.71 L·m -2 ·h -1 bar -1 .

[0041] Example 2

[0042] In this embodiment, the functionalized graphene quantum dots are graphene oxide quantum dots.

[0043] A method for preparing a porous graphene-based acid-resistant composite film comprises the following steps:

[0044] Step 1 is the same as step 1 of Example 1.

[0045] Step 2, preparation of porous graphene-based acid-resistant composite membrane: The graphene oxide quantum dots prepared by hydrothermal method were prepared into a solution with a concentration of 2.0 g·L -1 The polyethersulfone-based membrane was immersed in an aqueous solution with a concentration of 1.0 g·L as the aqueous phase for 8 min. After removing the excess liquid with a rubber roller, the membrane was immersed in an aqueous solution with a concentration of 1.0 g·L -1 The interfacial polymerization reaction was carried out in a toluene diisocyanate organic solution for 3 minutes. After the reaction was completed, the obtained membrane was placed in an oven at 45°C for heat treatment for 10 minutes to finally obtain a porous graphene-based acid-resistant composite membrane.

[0046] The prepared porous graphene-based acid-resistant composite membrane was subjected to 1.0 g·L -1 The interception rate of Congo red solution was 96.15% and the permeation flux was 198.31 L·m -2 ·h -1 bar -1 .

[0047] Example 3

[0048] In this embodiment, the functionalized graphene quantum dots are amino-modified graphene quantum dots.

[0049] A method for preparing a porous graphene-based acid-resistant composite film comprises the following steps:

[0050] Step 1 is the same as step 2 of Example 1.

[0051] Step 2, preparation of porous graphene-based acid-resistant composite membrane: The amination-modified graphene quantum dots prepared by hydrothermal method were prepared into a solution with a concentration of 1.0 g·L -1 of aqueous solution and added with a concentration of 0.15 g·L -1 The amphiphilic surfactant fatty alcohol polyoxyethylene sulfate sodium was added to obtain an aqueous phase solution. The polyethersulfone-based membrane was then immersed in the aqueous phase solution for 10 min. After removing the excess liquid with a rubber roller, the membrane was immersed in a concentration of 1.4 g·L -1 The interfacial polymerization reaction was carried out in an organic solution of hexamethylene diisocyanate for 2 minutes. After the reaction was completed, the obtained membrane was placed in an oven at 45°C for heat treatment for 10 minutes to finally obtain a porous graphene-based acid-resistant composite membrane.

[0052] The prepared porous graphene-based acid-resistant composite membrane was subjected to 1.0 g·L -1 The interception rate of Congo red solution was 98.02% and the permeation flux was 102.34 L·m -2 ·h -1 bar -1 .

[0053] Example 4

[0054] In this embodiment, the functionalized graphene quantum dots include graphene oxide quantum dots and amino-modified graphene quantum dots, and the mass ratio of the two is 1:1.

[0055] A method for preparing a porous graphene-based acid-resistant composite film comprises the following steps:

[0056] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1.

[0057] Step 3, preparation of porous graphene-based acid-resistant composite membrane: The graphene oxide quantum dots and amino-modified graphene quantum dots prepared by hydrothermal method were prepared into a solution with a concentration of 1.0 g·L -1 The two solutions were mixed in a 1:1 ratio and a concentration of 0.01 g·L -1 The amphiphilic surfactant sodium dodecyl sulfate was added to obtain a mixed aqueous phase solution. The polyethersulfone-based membrane was then immersed in the mixed aqueous phase solution for 10 min. After removing the excess liquid with a rubber roller, the membrane was immersed in a solution with a concentration of 1.4 g·L -1 The interfacial polymerization reaction was carried out in an organic solution of p-phenylene diisocyanate for 3 minutes. After the reaction was completed, the obtained membrane was placed in an oven at 45°C for heat treatment for 10 minutes to obtain a porous graphene-based acid-resistant composite membrane.

[0058] Figure 3The figure shows the surface electron microscope image of the porous graphene-based acid-resistant composite membrane. It can be seen that the membrane surface structure is smooth without obvious wrinkles. The concave hole structure shown on the membrane surface shows the pore morphology of the base membrane surface. These concave hole structures are not transparent, indicating that the formed surface separation layer is very thin and is not enough to cover the original pore morphology of the base membrane surface. Figure 4 Shown is a cross-sectional electron microscope image of the porous graphene-based acid-resistant composite membrane. It can be seen that it has an ultra-thin thickness of about 18 nm, which further proves the ultra-thin characteristics of the separation layer. The ultra-thinness of the separation layer is conducive to the improvement of the permeability performance.

[0059] The prepared porous graphene-based acid-resistant composite membrane was subjected to 0.1 g·L -1 The interception rate of Congo red solution was 99.23% and the permeation flux was 142.84 L·m -2 ·h -1 bar -1 , showing excellent separation performance. The membrane was subsequently immersed in 4% HCl and 10% HNO3 for 120 hours, and the retention rate of the dye was measured to be above 98%, showing excellent acid resistance.

[0060] Example 5

[0061] In this embodiment, the functionalized graphene quantum dots include oxidized graphene quantum dots and amino-modified graphene quantum dots, and the mass ratio of the two is 2:1.

[0062] A method for preparing a porous graphene-based acid-resistant composite film comprises the following steps:

[0063] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1.

[0064] Step 3, preparation of porous graphene-based acid-resistant composite membrane: The graphene oxide quantum dots and amino-modified graphene quantum dots prepared by hydrothermal method were prepared into a solution with a concentration of 2.0 g·L -1 The two solutions were mixed in a ratio of 2:1 and a concentration of 0.01 g·L -1 The amphiphilic surfactant sodium dodecyl sulfate was added to obtain a mixed aqueous phase solution. The polyethersulfone-based membrane was then immersed in the mixed aqueous phase solution for 10 min. After removing the excess liquid with a rubber roller, the membrane was immersed in a solution with a concentration of 1.6 g·L -1 The interfacial polymerization reaction was carried out in an organic solution of p-phenylene diisocyanate for 3 minutes. After the reaction was completed, the obtained membrane was placed in an oven at 45°C for heat treatment for 10 minutes to finally obtain a porous graphene-based acid-resistant composite membrane.

[0065] The prepared porous graphene-based acid-resistant composite membrane was subjected to 1.0 g·L -1The interception rate of Congo red solution was 99.13% and the permeation flux was 163.57 L·m -2 ·h -1 bar -1 .

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous graphene-based acid-resistant composite membrane, characterized in that: The following steps are involved: Step 1: dispersing functionalized graphene quantum dots in an aqueous solution to prepare an aqueous solution, wherein the concentration of the functionalized graphene quantum dots in the aqueous solution is 0.1 to 20 g·L -1 ; Step 2, immersing the basement membrane in the aqueous solution, taking out the basement membrane after immersion for a fixed time, and removing excess liquid, preferably, using a rubber roller to remove excess liquid; Step 3: Immerse the basement membrane treated in step 2 in a solution having a concentration of 0.1 to 20 g·L -1 In an organic phase solution of diisocyanate, an interfacial polymerization reaction is carried out; Step 4, heat-treating the membrane obtained after the treatment in step 3 to obtain a porous graphene-based acid-resistant composite membrane.

2. The preparation method according to claim 1, characterized in that In step 1, the functionalized graphene quantum dots are graphene quantum dots containing reactive functional groups, and the particle size thereof is 0.5 to 10 nm. Preferably, the reactive functional groups are amino, hydroxyl, sulfonic acid, epoxy, carbonyl or carboxylic acid groups.

3. The preparation method according to claim 1, characterized in that: The aqueous solution in step 1 further contains a surfactant, which is at least one of sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate, sodium secondary alkyl sulfonate, sodium dodecyl sulfonate or sodium fatty acid methyl ester sulfonate, and the concentration of the surfactant in the aqueous solution is 0.001-0.2 g·L -1 .

4. The preparation method according to claim 1, characterized in that: In the step 2, the base membrane is at least one of polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, nylon or polytetrafluoroethylene ultrafiltration / microfiltration membrane, and the immersion time is 5-15 minutes.

5. The preparation method according to claim 1, characterized in that: In the step 3, the diisocyanate is at least one of p-phenylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,4-phenylene diisocyanate or lysine diisocyanate.

6. The preparation method according to claim 1, characterized in that: In the step 3, the solvent of the organic phase solution is at least one of n-hexane, cyclohexane, n-heptane or isoalkane.

7. The preparation method according to claim 1, characterized in that: In the step 3, the time of the interfacial polymerization reaction is 10 to 300 seconds.

8. The preparation method according to claim 1, characterized in that: In step 4, the heat treatment temperature is 40-50° C., and the treatment time is 5-15 minutes.

9. A porous graphene-based acid-resistant composite membrane obtained by the preparation method as described in any one of claims 1 to 9.

10. The porous graphene-based acid-resistant composite membrane according to claim 9, characterized in that: The invention comprises a base film and a porous graphene film composited on the base film, wherein the porous graphene film is assembled on the surface of the base film by functionalized graphene quantum dots through interfacial polymerization, the functional groups at the edges of the functionalized graphene quantum dots are connected to isocyanate through polyurethane and polyurea structures, and the thickness of the porous graphene film is less than 50nm.

Citation Information

Patent Citations

  • Ceramic composite nanofiltration membrane for dye removal and preparation method thereof

    CN111672339A

  • Preparation method of high-flux composite nanofiltration membrane

    CN112007521A

  • membrane

    WO2018138486A1